2015
DOI: 10.1039/c4ra12943a
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antidiabetic activities of peptides isolated from a hydrolysate of an egg-yolk protein by-product prepared with a proteinase from Asian pumpkin (Cucurbita ficifolia)

Abstract: Bioactive peptides derived from food have been increasingly popular due to their therapeutic properties. Of particular importance are peptides with a multidirectional activity that can be used in the treatment and prevention of diet-related diseases. This paper attempts to utilize a by-product of phospholipid extraction from egg yolk as a source of peptides with a broad spectrum of biological activity. In addition, in this research we used a non-commercial enzyme obtained from Asian pumpkin, which has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…They further reported that one of the peptides, KLPGF, had the highest effect against a-glucosidase and a-amylase with IC 50 values of 59.5 § 5.7 and 120 §4.0 mmol¢l ¡1 , respectively (Yu et al, 2012). Moreover, Zambrowicz et al (2015) reported high level of anti-diabetic effects of bioactive peptides in a by-product of phospholipid extraction from egg yolk through inhibition of a-glucosidase and DPP-IV. They claimed that a peptide from the by-product, with amino acid sequence of LAPSLPGKPKPD, showed the strongest a-glucosidase inhibitory (1065.5 mmol¢l…”
Section: Anti-diabetic Effectmentioning
confidence: 99%
“…They further reported that one of the peptides, KLPGF, had the highest effect against a-glucosidase and a-amylase with IC 50 values of 59.5 § 5.7 and 120 §4.0 mmol¢l ¡1 , respectively (Yu et al, 2012). Moreover, Zambrowicz et al (2015) reported high level of anti-diabetic effects of bioactive peptides in a by-product of phospholipid extraction from egg yolk through inhibition of a-glucosidase and DPP-IV. They claimed that a peptide from the by-product, with amino acid sequence of LAPSLPGKPKPD, showed the strongest a-glucosidase inhibitory (1065.5 mmol¢l…”
Section: Anti-diabetic Effectmentioning
confidence: 99%
“…Findings on peptides derived from albumin [10] and egg white proteins [20] also suggested that the presence of proline and a basic amino acid (lysine and arginine) may be important for enhanced activity because RVPSLM, KLPGF, and TPSPR displayed higher α-glucosidase inhibition than other peptides investigated in both studies. [23,29,30] Although most of the peptides investigated for αglucosidase inhibition did not contain methionine, Yu et al [20] observed that RVPSLM (IC 50 = 23.07 μm) had much higher activity than RVPSL (IC 50 = >150.0 μm) clearly indicating a requirement for methionine for enhanced activity. [23,29,30] Although most of the peptides investigated for αglucosidase inhibition did not contain methionine, Yu et al [20] observed that RVPSLM (IC 50 = 23.07 μm) had much higher activity than RVPSL (IC 50 = >150.0 μm) clearly indicating a requirement for methionine for enhanced activity.…”
Section: Effects Of Chain Length Amino Acid Composition and Sequementioning
confidence: 99%
“…In fact, even the most potent peptide STYV (IC 50 = 0.012 μm) was digested to STY. This might be of great impact in the search of multifunctional antidiabetic peptides [4,29,31] as peptides of longer sequences can be designed which could release fragments with α-glucosidase and DPP-IV inhibitory activities after GIT digestion. Considering the activities and sequences of both peptides, minor structural and physicochemical changes may be needed to produce a highly active α-glucosidase inhibitory peptide that is resistant to GIT digestion.…”
Section: In Silico Simulated Gastrointestinal Digestion Of α-Glucosmentioning
confidence: 99%
“…In this, context comes the importance of natural remedial measures like the use of food-derived bioactive peptides. The antidiabetic peptide has also been reported in case of egg yolk protein hydrolysates [7]. These food-borne bioactive peptides can be produced by various methods like processing of food using various physical and chemical agents that hydrolyze proteins, treatment with various proteolytic enzymes, and by the activity of various microbes in case of fermented foods [8].…”
Section: Introductionmentioning
confidence: 99%